RANCANGAN SISTEM INFORMASI DATA PEMBAYARAN UANG KEHORMATAN KPU DAN HONORARIUM KELOMPOK KERJA (POKJA) KPU KABUPATEN TANJUNG JABUNG TIMUR - Sri Mulyati (JURNAL AKADEMIKA)
The accuracy of the information budget item, employee data as well as the withholding tax charged to process payment data aims to fulfill the right of employees to information amount of money Honorary manupun honorarium to be received and the amount of taxes to be paid over to the state treasury. Inaccuracies of information resulting from personnel administration system and information regarding the payment data can lead to errors in the calculation of the amount of fees to be paid to employees, inaccuracies co ncerning payment data can also be caused by the recording system Eyes Budget. It is necessary for applications that can address the weaknesses in data processing payments KPU honor.